Peningkatan Kompetensi Komunikasi SBAR Mahasiswa Keperawatan Melalui Pendampingan Dosen Klinik Di RSU. Haji Medan - Prodalima; Nadya Gusva (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Effective communication through the SBAR (Situation, Background, Assessment, Recommendation) method is a crucial component in improving patient safety and the quality of nursing care. However, nursing students often fail to systematically implement SBAR communication during clinical practice. This community service project aims to improve students' SBAR communication competency through mentoring-based training with an experiential learning approach at RSU Haji Medan. The method used was a pretest–posttest design without a control group involving 15 nursing students. The intervention was carried out through the stages of reinforcing the SBAR concept, direct mentoring in the treatment room, and observation- and reflection-based evaluation. Competency was measured using an observation sheet covering the aspects of Situation, Background, Assessment, Recommendation, communication clarity, and self-confidence. The results showed an increase in the average score from 65.6 in the pretest to 83.8 in the posttest, with an average increase of 18.2 points and all participants experienced an increase (100%). These findings indicate that experiential learning-based mentoring is effective in improving students' SBAR communication competency. In addition to improving individual skills, this program also contributes to building a culture of professional communication and supporting patient safety in the hospital environment